Do you remember? Similarities and differences between the earliest childhood memories for the five senses. Issue 3 (16th March 2021) - Hutmacher, Fabian
ABSTRACT: We perceive the world with our five senses. However, the role that these five senses play in early childhood memories has received relatively little attention. Against this background, participants ( N  = 117) were asked to write down their earliest childhood memories for the five senses and to answer additional questions regarding these memories. There was no significant difference between the five senses regarding the percentage of participants reporting a memory or between the valence and the subjective reliability of the reported memories. However, memories reported for sight were marginally longer, from a younger age, and estimated to be more important compared to memories reported for the other senses. A qualitative content analysis revealed that the vast majority of the reported memories fell into a limited number of categories. Interestingly, several categories played a role in more than one sense. Nevertheless, the reported memories also mirrored the characteristic properties that one is able to perceive with each sense. Overall, the findings support the notion that sight is the dominant sense. At the same time, they remind us that each sense provides us with unique information about ourselves and the world around us.